Exploring the Protective Effects and Mechanism of Crocetin From Saffron Against NAFLD by Network Pharmacology and Experimental Validation - Xu, Zijin; Lin, Susu; Gong, Junjie; Feng, Peishi; Cao, Yifeng; Li, Qiaoqiao; Jiang, Yuli; You, Ya; Tong, Yingpeng; Wang, Ping (Frontiers in Medicine, 2021)
Background：Nonalcoholic fatty liver disease (NAFLD) is a burgeoning health problem but no drug has been approved for its treatment. Animal experiments and clinical trials have demonstrated the beneficial of saffron on NAFLD. However, the bioactive ingredients and therapeutic targets are unclear. Purpose: This study aimed to identify the bioactive ingredients of saffron responsible for its effects on NAFLD and explore its therapy targets through network pharmacology combined with experimental tests. Methods: Various network databases were searched to identify bioactive ingredients of saffron and identify NAFLD-related targets. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment were conducted to enrich functions and molecular pathways of common targets and the STRING database was used to establish a protein-protein interaction network (PPI). The effect of crocetin (CCT) on NAFLD was evaluated in a mouse model of NAFLD by measuring the biomarkers of lipid, liver and renal function, oxidative stress, and inflammation. Liver histopathology was performed to evaluate liver injury. Nuclear factor erythroid-related factor (Nrf2) and hemeoxygenase-1 (HO-1) were examined to elucidate underlying mechanism for the protective effect of saffron against NAFLD. Results: A total of 9 bioactive ingredients, including CCT, with 206 common targets showed therapeutic effects on NAFLD. Oxidative stress and diabetes related signaling pathways were identified as the critical signaling pathways mediating the therapeutic effects of the active bioactive ingredients on NAFLD. Treatment with CCT significantly reduced the activities of aspartate aminotransferase (AST), alanine transaminase (ALT), and the levels of total cholesterol (TC), triglyceride (TG), malondialdehyde (MDA), blood urea nitrogen (BUN), creatinine (CR), and uric acid (UA). CCT significantly increased the activities of superoxide dismutase (SOD) and catalase (CAT). Histological analysis showed that CCT suppressed high-fat diet (HFD) induced fat accumulation, steatohepatitis, and renal dysfunctions. Results of ELISA assay showed that CCT decreased the expression of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), interleukin-1β (IL-1β), and increased the expression of HO-1 and Nrf2. Conclusion: This study shows that CCT is a potential bioactive ingredient of saffron that treats NAFLD. Its mechanism of action involves suppressing of oxidative stress, mitigating inflammation, and upregulating Nrf2 and HO-1 expression.